Novel molecularly imprinted magnetic nanoparticles for the selective extraction of protoberberine alkaloids in herbs and rat plasma. Issue 12 (7th May 2015) - Meng, Jiawei; Zhang, Wenpeng; Bao, Tao; Chen, Zilin
<x xml:space="preserve">Abstract</x> In this work, a novel magnetic nanomaterial functionalized with a molecularly imprinted polymer was prepared for the extraction of protoberberine alkaloids. Molecularly imprinted polymers were made on the surface of Fe3O4 nanoparticles by using berberine as template, acetonitrile/water as porogen, acrylamide as functional monomer and ethylene glycol dimethacrylate as cross‐linker. The optimized molar ratio of template/functional monomer was 1:7. The polymeric magnetic nanoparticles were characterized by transmission electron microscopy and Fourier transform infrared spectroscopy. The stability and adsorption capacity of the molecularly imprinted polymers were investigated. The molecularly imprinted polymers were used as a selective sorbent for the magnetic molecularly imprinted solid‐phase extraction and determination of jatrorrhizine, palmatine, and berberine. Extraction parameters were studied including loading pH, sample volume, stirring speed, and extraction time. Finally, a magnetic molecularly imprinted solid‐phase extraction coupled to high‐performance liquid chromatography method was developed. Under the optimized conditions, the method showed good linear range of 0.1–150 ng/mL for berberine and 0.1–100 ng/mL for jatrorrhizine and palmatine. The limit of detection was 0.01 ng/mL for berberine and 0.02 ng/mL for jatrorrhizine and palmatine. The proposed method has been applied to determine protoberberine alkaloids in Cortex phellodendri and rat plasma samples. The recoveries ranged from 87.33–102.43%, with relative standard deviation less than 4.54% in Cortex phellodendri and from 102.22–111.15% with relative standard deviation less than 4.59% in plasma.